Analysis of the roles and functions of the school social worker in Spain: evolution of legislation and types of intervention - Valero-Errazu, Diana; Romea, Ana C.; Palain-Pescador, Aranzazu (Acciones e Investigaciones Sociales, 2019)
Social work in a school environment is still relatively unknown in Spain, whereas in countries like the USA it has already accu- mulated over 100 years of history. Nevertheless, education is known to be one of the fields in which the direct impact of social work is evident at all levels, ranging from the individual to the family. This includes various social groups spawned by primary school, as well as those that emerge at community level. It is a fact that, in accordance with current educational legislation, social work can indeed be found in primary and secondary schools. However, in Spain it is rarely specified in the figure of the school social worker. In this study we review the social work performed in Spanish schools, to shed light on a facet of the profession that is invisible and still denied by a large number of professionals, who still confuse it with the work done by psychologists and school counselors. With this in mind, we look at the legislative development enjoyed by the social worker in the educational sector, in addition to analysing its functions in the fields and intervention models pertaining to social work.
Keywords: social work; school social work; education; technical teachers for community services; intervention models; legislative evolution